Perancangan Pusat Penjualan Bahan Bangunan Di Kota Makassar - Septiani Detuage; Abd. Azis Alimuddin; Ansarullah Ansarullah (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2023)
Design is a creation to obtain a result by taking an explicit action or a product of something with a physical reality. Building Materials Sales Center is a commercial building unit that is used as a building materials sales center that is established at a location that is planned, considered, initiated, and managed to become an operational unit related to the site, size, type of building, and the area of ​​expenditure of the team. This unit also provides parking lots that are made according to the kind of size the total required land requirement is As for those who follow development standards to fulfill building functions, as well as use buildings for a long time by choosing quality building materials and are willing to use delivery services from outside the city, as well as from outside Sulawesi, where shipping costs are pretty expensive.